Purification of glycoproteins from herpes simplex virus - Graham, Richard Peter (Division of Medical Microbiology, 2017)
The aim of this work was to purify type-specific glycoproteins from herpes simplex virus type 1 (HSV-1) and type 2 (HSV-2) for diagnostic use. The most likely candidate for a type-specific glycoprotein of HSV-1 is glycoprotein C (gC), although it has recently been shown to contain some type-common antigenic determinants. HSV-1 and HSV-2 were produced in BHK-21 cells and labelled with either (³H)-glucosamine ((³H)-gln) or a mixture of (¹⁴C)-amino acids ((¹⁴C)-aa). Analysis of the radiolabelled products by analytical sodium dodecyl sulphate polyacrylamide gel electrophoresis (SOS-PAGE) and autoradiography revealed that in the HSV-1 infected cells the radiolabelled components were incorporated into viral specific proteins only, whereas in the HSV-2 infected cells they were incorporated into host cell proteins as well as viral proteins. Preparative polyacrylamide gel electrophoresis (Prep-PAGE) was used as an initial step in separating HSV-1 infected cell proteins labelled with (³H)-gln. Two cycles of Prep-PAGE were sufficient to produce solutions containing either glycoprotein B ( gB) or glyco- protein C (gC), which were free of other HSV-1 glycoproteins. However, these solutions still contained a number of non-glycosylated proteins. Two different techniques were utilized to remove the non-glycosylated proteins from the glycoprotein solutions. Hydroxylapatite (HAUltrogel) chromatography in the presence of sodium dodecyl sulphate (SDS-HTP) did not separate the different HSV-1 glycoproteins and was not satisfactory for removing the non-glycosylated proteins. Gel-bound lectin affinity chromatography using wheat germ lectin and Helix pomatia lectin was not successful in purifying the glycoproteins because the glycoproteins which bound to the lectins could not be eluted under normal conditions. Difficulties encountered in eluting the HSV-1 glycoproteins from the lectins may have been due to the sodium dodecyl sulphate (SOS) in which the proteins were solubilized. For this reason, the gelbound lectin affinity chromatography was repeated using HSV-1 membrane proteins solubilized in a non-ionic detergent, Triton X-100. Using material prepared in this way, several HSV-1 glycoproteins were bound by wheat germ lectin and eluted under normal conditions to yield glycoproteins which were purified with respect to nonglycosylated proteins.